Existence of Solutions for Superlinear Second-Order System with Noninstantaneous Impulses - Yucheng Bu (Abstract and Applied Analysis)
Variational methods are used in order to establish the existence of nontrivial weak solution for superlinear second-order system with noninstantaneous impulses. The main result is obtained when a kind of definition of the weak solution for this system is introduced. Meanwhile, an example is presented to illustrate the main result.